Renal angiomyolipomas: At least two diseases. A series of patients treated at two European institutions. Issue 4 (April 2017) - Delhorme, J.-B.; Fontana, A.; Levy, A.; Terrier, P.; Fiore, M.; Tzanis, D.; Callegaro, D.; Dratwa, C.; Gronchi, A.; Bonvalot, S.
Abstract: Objective: The aim of this study is to analyze the outcome of renal angiomyolipomas (AML) at two European institutions. Methods: The data were collected from patients with a primary AML who were treated at Gustave Roussy, Villejuif, France and Fondazione IRCCS Istituto Nazionale dei Tumori in Milan, Italy from 1998 to 2014. The specimens were classified as classic AML (C AML) or epithelioid AML (E AML) based on the percentage of epithelioid cells. Results: There were 40 patients identified for the study (35 C AML, 5 E AML). One patient had an associated tuberous sclerosis complex. Six patients (15%) had bilateral AML. The imaging results were significantly different between C/E AML. E AML was associated with fewer bilateral lesions, more renal vein/vena cava extension, and more poor or non-fatty aspects. Surgery/active surveillance (AS)/chemo radiation were applied for 28/11/1 patients, respectively. The median tumor size was significantly smaller (3.75 cm) in patients receiving AS (median 15 cm when surgically resected). The median patient follow-up was 43 months. The three-year overall survival was significantly better for patients with C AML than E AML (100% versus 50%, p < 0.0001). The univariate analysis identified the OS prognostic factors were E AML histologic subtype (p < 0.001), poor/non fatty features (p = 0.002), and renal vein extension on imaging (p = 0.01). Conclusion: AML manifests as at least two different entities with significantly different outcomes. Epithelioid subtype, poor/non-fatty features, and renal vein involvement are all associated with worse survival.